(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the pattern of oral squamous cell carcinoma in patients presenting at LUH Hyderabad Sindh. Study Design: Descriptive Study Place and Duration of Study: This study was conducted at Oral Surgery Department, LUH Hyderabad, Sindh from January 2011 to December 2011. Materials and Methods: Present study was done on 144 cases. Patients with biopsy proven oral squamous cell carcinoma of all age group and gender were included in the study. radiated, benign, metastatic tumers were expelled from study. Results: Out of 144 patients, 80 (55.5%) were females and 64(44.4%) were males. Mean age group was 31-40 years of age 50 (34.7%). the majority frequent site was Buccal mucosa 44 (30.5%). 120 (83.3%) patients were having well differentiated oral squamous cell carcinoma and slightest frequent type was poorly differentiated oral squamous cell carcinoma 4 (2.77%) cases. Conclusion: This study gives detailed account of oral squamous cell carcinoma as regards widespread age, Gender, Location and histological type of lesion.